Biotechnology for Biofuel Production. - Viele, B.; Ellingston, R.; Wang, D.; Park, Y.; Higgins, R.; Coleman, H. D.
The commercial production of lignocellulosic biofuels relies heavily on a reduction in production costs. These costs are high in part due to the challenge of biomass deconstruction and the complex nature of the secondary cell wall. The removal of lignin from the carbohydrates, and the subsequent or concurrent hydrolysis of the polysaccharides into monomers for fermentation continue to hamper large commercialization efforts. One solution for this is to tailor biomass for the production of fuels. Here we review work in the field of plant biotechnology, with a focus on dicots, to alter the secondary cell wall, produce plant made enzymes, increase biomass production, and create sterile lines. We conclude by laying out future directions for research to support the production of cost-effective lignocellulosic fuels.
Keywords: BIOTECHNOLOGY; BIOFUEL